2011
DOI: 10.1901/jaba.2011.44-999
|View full text |Cite
|
Sign up to set email alerts
|

Review of Sports Performance Research With Youth, Collegiate, and Elite Athletes

Abstract: This brief review summarizes translational and intervention research in the area of sports performance. We describe studies with youth, collegiate, and elite athletes; identify recent trends; and propose recommendations for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
(28 reference statements)
0
21
0
1
Order By: Relevance
“…Research in applied behavior analysis has focused on sports for many years, and research using single-subject designs for sports has increased over the past 30 years (Luiselli, Woods, & Reed, 2011;Martin et al, 2004). Behavioral research to enhance sports performance has been conducted in numerous sports domains, including football, tennis, soccer, gymnastics, ballet, speed skating, and rowing (Martin et al, 2004).…”
mentioning
confidence: 99%
“…Research in applied behavior analysis has focused on sports for many years, and research using single-subject designs for sports has increased over the past 30 years (Luiselli, Woods, & Reed, 2011;Martin et al, 2004). Behavioral research to enhance sports performance has been conducted in numerous sports domains, including football, tennis, soccer, gymnastics, ballet, speed skating, and rowing (Martin et al, 2004).…”
mentioning
confidence: 99%
“…In particular, at the general motor level, they have improved body orientation skills in space; at the specific technical and tactical level, through the collaboration between multiple players and the choice of solutions depending on the handball, the teammates and the defenders. The results of the research showed a general improvement in performance (Luiselli, Woods, 2011), validating the choice of additional training methods. At the end of the competitive season, the data processed showed that the percentages of increase in passing and shooting percentages improved about 14% for group B. Referencees Achenbach L., Krutsch V., Weber J., Nerlich M., Luig P., Loose O., Angele P., Krutsch W. (2017), Neuromuscular exercises prevent severe knee injury in adolescent team handball players, Knee Surg Sports Traumatol Arthrosc., Oct 20. doi: 10.1007/s00167-017-4758-5 Altavilla G., Tafuri D., Raiola G. (2014), Influence of sports on the control of static balance in physical education at school, Journal of Physical Education and Sport, 14 (3), pp.…”
Section: Discussionmentioning
confidence: 63%
“…Luiselli, Woods, and Reed () indicated that future research should evaluate social validity of sports performance intervention and procedures. Allowing external experienced coaches to review baseline videos and training videos provided insight to how expert coaches would evaluate improvements following BST.…”
Section: Discussionmentioning
confidence: 99%